Diagnostic Variability of Laryngeal Premalignant Lesions: Histological Evaluation and Carcinoma Transformation. (23rd December 2013) - Hu, Yanping; Liu, Honggang
Abstract : Objective: This study was to analyze the interobserver histopathological variability and carcinoma transformation of laryngeal premalignant lesions. Study Design: A historical cohort study. Setting: Department of Pathology, Beijing TongRen Hospital, Capital Medical University, Beijing, China. Subjects and Methods: κ‐statistics analysis was performed to estimate interobserver histopathological variability among pathologists by reassessment of 237 cases with laryngeal premalignant lesion according to 2005 WHO classification system. A retrospective follow‐up of 237 patients over 8‐year duration was carried out, and the carcinoma transformation of laryngeal premalignant lesions was analyzed using Kaplan‐Meier survival curve estimation. Results: κ‐values of 0.5989 concerning interobserver variability indicated a moderate agreement among 3 pathologists. Major source of intergrade diagnostic disagreement between the original and the consensus diagnoses involved 2 grade pairs, namely, mild and moderate dysplasia, severe dysplasia, and carcinoma in situ. In addition, follow‐up study showed that 20 of 237 (8.44%) laryngeal premalignant lesion cases developed into invasive carcinoma. Carcinoma transformation in severe dysplasia group exhibited a similar risk compared to that in carcinoma in situ group ( P =. 232). Conclusion: Severe dysplasia shows the same carcinoma transformation potential as the carcinoma in situ does. Clinically, more attention to severe dysplasia is needed in comparison with mild and moderate dysplasia.